Creación de una oficina de capacitación y asesoramiento en gestión secretarial en la ciudad de Machala. - Romero Barragan, Erika Alexandra (My University, 2019)
The secretarial profession is linked to the administrative area, being therefore a highly important profession within the activities of every successful company. Like any profession, continuous training and education is necessary in order to enrich and improve the capacities and skills of the secretaries. The role of the executive secretary has achieved new dimensions, as a result of technological advances and automation, increasing the need for human talent that excels in new areas, which means greater responsibility in its functions and therefore must be more productive in the development of their tasks, working with professional ethics to help the administration, In this way, companies have to be prepared to the demands of the market and therefore keep professionally trained their workers. The training of the personnel of an organization "is key for the survival and adaptability of the organizations to the changes that are being generated, converting it into a competitive advantage; where human capital has the ability to change the rest of the members of the company. " From the point of view of the company, the continuous training of the worker of the secretarial area is integrated within the company's own strategy, "since they are a fundamental pillar for the administrators in their daily tasks; being a support that coordinates, moderates and inspires decision-making; it is the image of his superior and in some cases of the company itself ". The training of personnel in the secretarial area becomes an advantage for the company, having workers who have knowledge in the management of administrative tasks, office supervision, communication, human resources management, and many others. skills. At present, entrepreneurship is extremely important for society, since it allows the search for innovations and transformations of knowledge for the creation of new goods and services. To start an enterprise, an idea of a product, service or process is required, hardworking people who support the initiative, a clear procedure for the preparation of the product or service provision, sources of financing. Entrepreneurship is important because it is the best way to grow economically, to be independent, and to have a quality of life according to our expectations. Entrepreneurship makes a society have a better development. The purpose of the market study is to analyze the characteristics of the demand, as well as the competence of an organization in order to have an idea of its commercial viability. "It helps to estimate market share; analyzes the buying behavior of the public and measures the efficiency in the determination of prices of goods and services "In this sense, the objective of the research is to establish a business plan for the creation of a company that provides training and advisory services in the area of secretarial management. The methodology used consisted in the review and analysis of bibliographic sources. The study design had a quantitative-qualitative approach. The techniques applied were the survey for the market study and mathematical-financial procedures for the feasibility study. The population studied was the professionals in the area of executive secretariat. The results obtained indicate that the project to create a training and advisory office for secretarial management in the city of Machala is technically feasible. At a financial level, the venture is viable because the net present value gave a positive result. The IRR is greater than the cost of capital. The recovery of the investment is about 2 years and if it generates benefits. To start a business requires an idea of a product, service or process, hardworking people who support the initiative, a clear procedure for product development or service provision , sources of financing. Entrepreneurship is important because it is the best way to grow economically, to be independent, and to have a quality of life according to our expectations. Entrepreneurship makes a society have a better development. The purpose of the market study is to analyze the characteristics of the demand, as well as the competence of an organization in order to have an idea of its commercial viability. "It helps to estimate market share; analyzes the buying behavior of the public and measures the efficiency in the determination of prices of goods and services "In this sense, the objective of the research is to establish a business plan for the creation of a company that provides training and advisory services in the area of secretarial management. The methodology used consisted in the review and analysis of bibliographic sources. The study design had a quantitative-qualitative approach. The techniques applied were the survey for the market study and mathematical-financial procedures for the feasibility study. The population studied was the professionals in the area of executive secretariat. The results obtained indicate that the project to create a training and advisory office for secretarial management in the city of Machala is technically feasible. At a financial level, the venture is viable because the net present value gave a positive result. The IRR is greater than the cost of capital. The recovery of the investment is of 2 years approximately and if it generates benefits.
La profesión secretarial está vinculada con el área administrativa, siendo por tanto una profesión altamente importante dentro de las actividades de toda empresa exitosa. Como toda profesión, es necesario una formación y capacitación continua, a fin de enriquecer y mejorar las capacidades y aptitudes de las secretarias. El rol de la secretaria ejecutiva ha conseguido nuevas dimensiones, como resultado de los avances tecnológicos y la automatización, incrementando la necesidad de talento humano que sobresalga en nuevas áreas, lo que significa una mayor responsabilidad en sus funciones y por ende debe ser más productivo en el desarrollo de sus tareas, trabajando con ética profesional para ayudar a la administración, De esta manera, las empresas tienen que estar preparadas a las exigencias del mercado y por ende mantener capacitados profesionalmente a sus trabajadores. La capacitación del personal de una organización “es clave para la supervivencia y adaptabilidad de las organizaciones a los cambios que se están generando, convirtiéndola en una ventaja competitiva; donde el capital humano tenga la habilidad de cambiar al resto de los integrantes de la empresa”. Desde el punto de vista de la empresa, la formación continua del trabajador del área de secretariado se encuentre integrada dentro de la propia estrategia de la empresa, “ya que son un pilar fundamental para los administradores en sus tareas cotidianas; siendo un apoyo que coordina, modera e inspirara en la toma de decisiones; es la imagen de su superior y en algunos casos de la propia empresa”. La capacitación del personal del área de secretariado se convierte en una ventaja para la empresa, al contar con trabajadores que posean conocimientos en el manejo de las tareas administrativas, la supervisión de la oficina, la comunicación, la gestión de recursos humanos, y muchas otras habilidades. En la actualidad el emprendimiento es sumamente importante para la sociedad, ya que permite la búsqueda de innovaciones y transformaciones de los conocimientos para la creación de nuevos bienes y servicios. Para iniciar un emprendimiento se requiere una idea de un producto, servicio o proceso, personas trabajadoras que apoyen la iniciativa, un procedimiento claro para la elaboración de producto o prestación del servicio, fuentes de financiamiento. Es importante el emprendimiento ya que es el mejor camino para crecer económicamente, para ser independientes, y para tener una calidad de vida acorde a nuestras expectativas. El emprendimiento hace que una sociedad tenga un mejor desarrollo. El estudio de mercado tiene por finalidad analizar las características de la demanda, así como la competencia de una organización para de esta forma tener una idea de su viabilidad comercial. “Ayuda a estimar la participación en el mercado; analiza la conducta de compra del público y mide la eficacia en la determinación de precios de los bienes y servicios” En este sentido, el objetivo de la investigación es establecer un plan de negocios para la creación de una empresa que preste servicios de capacitación y asesoría en el área de gestión secretarial. La metodología utilizada consistió en la revisión y análisis de fuentes bibliográficas. El diseño del estudio tuvo un enfoque cuanti- cualitativo. Las técnicas aplicadas fueron, la encuesta para el estudio de mercado y procedimientos matemáticos-financieros para el estudio de factibilidad. La población objeto de estudio fueron las profesionales en el en el área de secretariado ejecutivo. Los resultados obtenidos indican que el proyecto de creación de una oficina de capacitación y asesoramiento en gestión secretarial en la ciudad de Machala es viable desde el punto de vista técnico. A nivel financiero, el emprendimiento es viable debido a que el valor actual neto dio un resultado positivo. La TIR es superior al costo de capital. La recuperación de la inversión es de 2 años aproximadamente y si genera beneficios. Para iniciar un emprendimiento se requiere una idea de un producto, servicio o proceso, personas trabajadoras que apoyen la iniciativa, un procedimiento claro para la elaboración de producto o prestación del servicio, fuentes de financiamiento. Es importante el emprendimiento ya que es el mejor camino para crecer económicamente, para ser independientes, y para tener una calidad de vida acorde a nuestras expectativas. El emprendimiento hace que una sociedad tenga un mejor desarrollo. El estudio de mercado tiene por finalidad analizar las características de la demanda, así como la competencia de una organización para de esta forma tener una idea de su viabilidad comercial. “Ayuda a estimar la participación en el mercado; analiza la conducta de compra del público y mide la eficacia en la determinación de precios de los bienes y servicios” En este sentido, el objetivo de la investigación es establecer un plan de negocios para la creación de una empresa que preste servicios de capacitación y asesoría en el área de gestión secretarial. La metodología utilizada consistió en la revisión y análisis de fuentes bibliográficas. El diseño del estudio tuvo un enfoque cuanti- cualitativo. Las técnicas aplicadas fueron, la encuesta para el estudio de mercado y procedimientos matemáticos-financieros para el estudio de factibilidad. La población objeto de estudio fueron las profesionales en el en el área de secretariado ejecutivo. Los resultados obtenidos indican que el proyecto de creación de una oficina de capacitación y asesoramiento en gestión secretarial en la ciudad de Machala es viable desde el punto de vista técnico. A nivel financiero, el emprendimiento es viable debido a que el valor actual neto dio un resultado positivo. La TIR es superior al costo de capital. La recuperación de la inversión es de 2 años aproximadamente y si genera beneficios.
Keywords: GESTIÓN SECRETARIAL; EMPRESA; FORMACIÓN